2014
DOI: 10.1186/1471-2458-14-1299
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for diabetes and diabetic retinopathy: results from the Nigeria national blindness and visual impairment survey

Abstract: BackgroundIn Nigeria, urbanisation and increasing life expectancy are likely to increase the incidence of non-communicable diseases. As the epidemic of diabetes matures, visual loss from diabetic retinopathy (DR) will increase unless mechanisms for early detection and treatment improve, and health systems respond to the growing burden of non-communicable diseases.MethodsA nationally-representative population-based sample of 13,591 participants aged ≥40 years selected by multistage-stratified-cluster-random-sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
51
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 46 publications
6
51
2
Order By: Relevance
“…In the present study, we identified a combination of risk factors that associated with diabetes. Interestingly, the strong association of DM with several risk factors was observed in our study, which is in agreement with other studies in many parts of the world [10,12,24,25] (Valdez, Yoon, Liu, & Khoury, 2007;Zhao et al, 2012;Connor et al, 2013;Kyari et al, 2014). In the present study, the frequency of DM was slightly higher among men (14.7%) compared to women (10.8%).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, we identified a combination of risk factors that associated with diabetes. Interestingly, the strong association of DM with several risk factors was observed in our study, which is in agreement with other studies in many parts of the world [10,12,24,25] (Valdez, Yoon, Liu, & Khoury, 2007;Zhao et al, 2012;Connor et al, 2013;Kyari et al, 2014). In the present study, the frequency of DM was slightly higher among men (14.7%) compared to women (10.8%).…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, a relationship between growing per capita income and economic development on the increase in diabetes prevalence have been well documented (Sherif & Sumpio, 2015). The current published literatures shown that there are several risk factors related to the development of diabetes and its complications (Midhet, Al-Mohaimeed & Sharaf, 2010;Zhao et al, 2012;Salam & Siddiqui, 2013;Kyari et al, 2014). Hence, it is very important to determine associated risk factors to prevent or delay the onset of DM as well as to avoid the existence of life-threatening complications (Zhao et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes mellitus is a public health problem because of its increasing prevalence and the complications it creates [1]. These complications include the retinopathy that is the set of consecutive retinal lesions or related to diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the prevalence rate was higher in comparison to Ghana and Nigeria, and lower in comparison to Kenya, which could be due to differences in population size, exposures to risk factors and study designs [9,10,[17][18][19][20] respectively. This is a pattern observed in other studies in Africa, which could reflect the ageing population in Africa [8,17]. By contrast, in our study, this association was not statically significant.…”
Section: Discussionmentioning
confidence: 99%